Penyelesaian Sengketa di dalam Hukum Pasar Modal - Sirait, Nadilla; Siregar, Emiel Salim; Sari, Dessy Indah; Sitorus, Andini Cahayani; Hasibuan, Haris Fadila; Ayusri, Ari; Sitorus, Arina Rofiqoh; ., Bakti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The capital market is an organized financial system that brings together shareholders and investors who had a certain period, directly or through intermediaries. The capital market sector is one of the financial services sectors that has a significant role in national development. Nowadays, lots of criticisms of capital market dispute resolution caused by many factors related to law enforcement, so efforts to create an orderly and efficient capital market have not been optimally achieve. In writing this researches the method used refers to normative juridical, which contains many juridical reviews from several sources and references to the object under study. In writing this article, a juridical approach used to get conclusions and keywords that are very precise from the object of studies in this article.